2013
DOI: 10.1590/s1413-81232013000300023
|View full text |Cite
|
Sign up to set email alerts
|

Políticas públicas de saúde do trabalhador: análise da implantação de dispositivos de institucionalização em uma cidade brasileira

Abstract: Políticas públicas de saúde do trabalhador: análise da implantação de dispositivos de institucionalização em uma cidade brasileiraPublic health policies for workers: analysis of the implementation of institutionalization measures in a Brazilian city

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
0
3
0
9
Order By: Relevance
“…In accordance with the existing public policies, this study showed that, with regard to treatment of cases identified, these were often refered to the Network of Psychosocial Attention, especially to CAPS, mental health and primary health care outpatient clinics. But it was also significant the number of CERESTs which worked under the support logic, as a gateway to workers, with a clinic for care and treatment of harms to workers' health, as noted also in other studies 30,33,34 . The fact that mental health professionals are often trained and prepared to act individually 13 may contribute to this, for usually they are not prepared to develop collective initiatives in which work is an important factor for building subjectivity.…”
Section: Discussionmentioning
confidence: 65%
“…In accordance with the existing public policies, this study showed that, with regard to treatment of cases identified, these were often refered to the Network of Psychosocial Attention, especially to CAPS, mental health and primary health care outpatient clinics. But it was also significant the number of CERESTs which worked under the support logic, as a gateway to workers, with a clinic for care and treatment of harms to workers' health, as noted also in other studies 30,33,34 . The fact that mental health professionals are often trained and prepared to act individually 13 may contribute to this, for usually they are not prepared to develop collective initiatives in which work is an important factor for building subjectivity.…”
Section: Discussionmentioning
confidence: 65%
“…Os representantes de sindicatos e usuários elencam uma série de dificuldades, a começar por problemas políticos e de gestão, caracterizados pela falta de continuidade na gestão, ou a política de "esvaziar gavetas" do CEREST-CE, pois, a cada troca de secretário de saúde, troca-se o coordenador do Centro, o que impede, não só a concretização dos objetivos, mas a fluidez das ações em saúde do trabalhador. Isso porque os indicados para o cargo não necessariamente incorporam a proposta institucional do programa, ou seja, o mero assistencialismo sobrepujou, cedendo espaço para ações médico/curativa/assistencialista (Leão & Castro, 2013). Assim sendo, é possível perceber certa subordinação da Política de Saúde do Trabalhador aos interesses políticos partidários, o que acaba por impossibilitar, por vezes, a trajetória de uma saúde do trabalhador mais eficaz no Ceará.…”
Section: Discussionunclassified
“…A RENAST constitui-se como uma rede de cobertura nacional e tem como objetivo a criação dos Centros de Referência em Saúde do Trabalhador (CERESTs) e como instrumento estratégico a difusão dos princípios e práticas do campo da Saúde do Trabalhador no SUS, em todos os níveis de atenção (Dias & Silva, 2013;Leão & Castro, 2013; Ministério da Saúde [MS], 2009;Quilião, Fassa, & Restrepo, 2013).…”
Section: Introductionunclassified
“…Of the health grievances related to labour, attention is drawn to labour accidents, recognized events, per Gessner et al (2013), as a public health problem, given the potential to cause deleterious effects to worker health. A series of measures, policies and risk control strategies and protection of workers has been implemented over the years in order to reduce, or even eliminate, the exposure to risk factors capable of causing accidents (leÃo;caStro, 2013).…”
Section: Introductionmentioning
confidence: 99%